Neutropenıa Secondary to Sars-Cov2 Vaccınatıon in Post-Hematopoıetıc Stem Cell Transplant (Hsct) Patıents - LUIS MIGUEL JUAREZ-SALCEDO; Samantha Feijóo; Cristina García; Alejandro Alonso; Beatriz Aguado; Javier Ortiz; Angela Figuera; Rafael de la Cámara (Mediterranean Journal of Hematology and Infectious Diseases)
SARS-Cov2 s, caused a high mortality in patients with some degree of immunosuppression, like those that receive a hematopoietic progenitor transplant. Since December 2020, several vaccines have been developed having been key in decreasing complications and mortality in this group of patients. Different articles have described the presence of thrombopenia related to the administration of vaccines, however, there are few data on the occurrence of neutropenia as a side effect after administration. We present several cases of neutropenia (defined as absolute neutrophil count (ANC) less than 2,000/mm3), after vaccination in hematopoietic progenitor transplant (HPT) recipients performed in our center during 2021.